Faktor-Faktor yang Mempengaruhi Kepatuhan Wajib Pajak Orang Pribadi (Studi Kasus Pada Masyarakat di Kabupaten Jepara) - Ghea Norma Gupita; Subadriyah Subadriyah (Jurnal Rekognisi Akuntansi, 2021)
This study aims to determine the effect of tax authorities service quality, taxpayer awareness, and the effectiveness of the tax system on individual taxpayer compliance in Jepara. The object used in Jepara Regency, for the population, namely individual taxpayers registered at KPP Pratama Jepara. Whereas in selection of sample using a random sampling method with the number of samples obtained, there are 100 respondents. For data analysis method used is multiple linear regression analysis with data analysis test consisting of data quality analysis and classical assumption test. In hypothesis using the coefficient of determination test, and statistical test t. The results of this study indicate that 1) Quality of Fiskus Services does not affect taxpayer compliance. 2) Taxpayer Awareness do not affect the Complience Taxpayer. 3) The Effectiveness of the Taxation System Has a Positive and Significant Effect on Taxpayer Compliance in Jepara Regency.